A pharmaceutical innovation: Is it worth the money? Whose money? - Michèle Sennhauser; Peter Zweifel (University of Zurich, Socioeconomic Institute, 2009)
This study seeks to provide evidence for deciding whether or not a pharmaceutical innovation should be included in the benefit list of social health insurance. A discrete choice experiment (DCE) was conducted in Germany to measure preferences for modern insulin therapy. Of the 1,100 individuals interviewed in 2007, 200 suffered from type 1 diabetes, 150 from insulin-treated type 2 diabetes, and 150 from insulin-naive type 2 diabetes. The long-acting insulin analogue 'Insulin Detemir' is compared to human insulin as the status quo. The DCE contains two price attributes, copayment and increased contributions to health insurance. As one would expect, non-affected non-diabetics and insulin-naive diabetics exhibit higher willingness-to-pay (WTP) values through copayment (adjusted for probability of contracting diabetes), while affected type 1 and insulin-treated type 2 diabetics have higher WTP through increased contributions. However, WTP values exceed the extra treatment cost in both financing alternatives, justifying inclusion of the innovation in the benefit list from a cost-benefit point of view.
Keywords: I11; H51; I18; 330; health insurance; discrete-choice experiment; preferences; diabetes; Innovation; Pharmazeutisches Produkt; Diskrete Entscheidung; Gesundheitsversorgung; Test; Deutschland